Addressing Patients' Alcohol Consumption-A Population-Based Survey of Patient Experiences - Torgeir Gilje Lid; Torgeir Gilje Lid; Nadine Karlsson; Kristin Thomas; Janna Skagerström; Amy O'Donnell; Latifa Abidi; Per Nilsen (Frontiers Media S.A., 2021)
Objectives: To identify the proportion of the population that had experienced that alcohol was addressed in health care the previous year, to explore experiences and perceived effects of addressing alcohol, and to investigate the proportion of risky drinkers in the population.Methods: Cross-sectional national web-based survey with 1,208 participants. Socio-demographic data, alcohol consumption (AUDIT-C), and experiences with alcohol conversations were investigated.Results: Approximately four in five respondents had visited health care the past 12 months, and one in six reported having experienced addressing alcohol. Women and older respondents were less likely to report having experienced alcohol conversations compared to other groups. Risky drinkers were not more likely to have experienced an alcohol conversation, but reported longer duration of alcohol conversations and more frequently perceived addressing alcohol as awkward or judgmental. Almost a third of respondents were classified as risky drinkers.Conclusion: The proportion experiencing addressing alcohol in routine health care is low, also among risky drinkers, and risky drinkers more frequently experienced the conversations as judgmental. More sensitive and relevant ways of addressing alcohol in health care is needed.